(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Solar energy is a big source of renewable energy and, luckily, solar energy is very rich in Egypt and the eastern Mediterranean region.The validation of the global solar radiation from the reanalysis data ECMWF-ERA5 by using the parameters from data elements and to deduce a new model to give a good representation of the GSR distribution when compared with measured data. The estimation of global solar radiation (GSR) distribution over Egyptduring the period time from 2017 to 2019. Evaluated and a comparative assessment of the models was carried out using measured GSR at Helwan (29.82 ᵒN, 31.29ᵒE) and Suez(31ᵒN.32ᵒE) sites are done. Database:The European Center for Middle-Distance Weather Forecast recently released its most complex reanalysis product ERA5 data set (ECMWF). This method has been developed and manufactured, giving it more advantages than ECMWF’s previously released ERA-Interim reanalysis products. It has better spatial resolution, can be archived every hour, and uses more advanced assimilation methods and merges more data sources. The results showed that the model could predict the pattern of the measured monthly, daily mean of GSR for the entire period. The correlation coefficient (R) is equal 95% and 97% of GSR for Helwan and Suez respectively.The outputs from our proposed model for monthly global solar radiation distribution over the period of study is given, and the maximum value 7.5 KWh/m2and the minimum are 3 KWh/m2.The values of RMSE of GSR-ERA5 and GSR-estimated for Helwan and Suez sites are 0.275, 0.446 and 0.2, 0.36 (KWh/m2) respectively. The values of MABE of GSR-ERA5 and GSR-estimated for the two station Helwan and Suez is 0.014, 0.023 and 0.007, 0.03 (KWh/m2) respectively. Finally the proposed model was used to givean indication of theGSR distribution over Egypt.